(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Jobsatisfaction is one of the most widely discussed issues in organizationalbehavior, personnel and human resource management and organizationalmanagement. As teaching does require a great deal of thoroughness and commitment, so in teaching it is more importantto have mental commitment and loyalty than physical presence. In this study theresearcher investigated the present level of job satisfaction among the facultymembers of university of Hyderabad. The major purpose of this descriptive-correlational study was to examine factors affectingjob satisfaction of faculty members ofUniversity of Hyderabad which is explained by Herzberg job motivator andhygiene factors. A random sample of 120 faculty member of Hyderabad Universitywas selected as a statistical sample. Employing a descriptive-correlativesurvey method and data were collected through questionnaire. The facultymembers were generally satisfied with their jobs. However, male faculty memberswere less satisfied than female faculty members. The factor “work itself” wasthe most motivating aspect for faculty. The least motivating aspect was“working conditions.” The demographic characteristics were negligibly relatedto overall job satisfaction. The factors “work itself,” and “advancement”explained 60 percent of the variance among faculty members’ overall level ofjob satisfaction. The demographic characteristics (age, years of experience,academic rank, degree) were negligibly related to overall job satisfaction.